PROPERTIES OF AVIATION BIOFUELS BASED ON BIO-ADDITIVES OF PLANT ORIGIN - Yakovleva, Anna; Pavlovskyi, Maksym; Zubenko, Stepan; Boshkov, Vasyl; Maksymiv, Oleh (Science-based technologies, 2023)
The paper is devoted to the study of the physicochemical properties of aviation biofuels, in particular, to the substantiation of the influence of bio-additives based on various vegetable oils on the properties of jet fuels and to the assessment of the possibility of using new bio-additives to produce aviation biofuels. The aviation industry’s current state is considered and its development’s key directions are presented. Considering the tasks of minimizing the environmental impact of aviation, decarbonizing the aviation sector and increasing its energy efficiency, one of the industry’s main priorities is the development of technologies for the production of alternative aviation fuels and their practical use. This paper considers alternative aviation fuels (biofuels), which are a mixture of traditional aviation fuels and bio-additives derived from various vegetable oils. Taking into account the trends of active transition from first-generation biofuels to second- and third-generation biofuels, the article considers new types of plant raw materials for obtaining bio-additives to fuels. In particular, the possibilities of using bio-additives based on palm kernel and coconut oils to produce second-generation biofuels are considered. The chemical composition and physicochemical properties of bio-additives based on various vegetable oils were investigated and analyzed. It is shown that the quantitative and qualitative composition of bio-additives determines their physicochemical properties. Further, the physicochemical properties of aviation biofuel samples based on petroleum aviation fuel and bio-additives were investigated. It is shown that the introduction of bio-additives into the composition of petroleum aviation fuels leads to changes in their properties, in particular, to an increase in density, viscosity, and crystallization temperature. The experimental results substantiate that bio-additives based on palm kernel and coconut oils have better characteristics than the previously studied bio-additives (based on rapeseed and castor oils), in particular, regarding the possibility of their use as components of aviation biofuels. Thus, the new bio-additives can be successfully used for further research on the development of alternative aviation fuels.